Teachers’ Understanding of Bullying - Mishna, Faye; Scarcello, Iolanda; Pepler, Debra; Wiener, Judith (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
Using semi‐structured interviews, we examined teachers’ understanding of bullying of children in their classes. Although teachers’ definitions of bullying included both direct and indirect behaviours, several factors influenced how they characterized and responded to incidents. These factors included whether the teachers viewed an incident as serious or considered a victimized child responsible, whether a child matched their assumptions about victim characteristics and behaviours, and whether they described feeling empathy for a child. The nature of the school environment and organization such as availability of systemic support in addressing bullying incidents were further factors that influenced teachers’ awareness and responses. Key words: peer victimization, qualitative study on bullying, understanding bullying, response to bullying À l’aide d’entrevues semi‐structurées, les auteures ont étudié comment les enseignants perçoivent l’intimidation dans leurs classes. Bien que leurs définitions de l’intimidation comprennent à la fois les comportements directs et indirects, plusieurs facteurs influencent leur façon de caractériser les incidents et d’y réagir, notamment s’ils considèrent que l’incident est sérieux ou que la victime est responsable, si la victime correspond à leurs théories implicites sur les caractéristiques et les comportements d’une victime et s’ils ressentent de l’empathie pour la victime. Le climat de l’école et les structures offertes tel un soutien systémique pour faire face aux incidents d’intimidation faisaient également partie des facteurs ayant une incidence sur la sensibilisation et les réactions des enseignants. Mots clés: victimisation par des pairs, étude qualitative sur l’intimidation, comprendre l’intimidation, réagir à l’intimidation.